Factor Structures of Patient Health Questionnaire-9 Instruments in Exploring Depressive Symptoms of Suburban Population - Vu, Linh Gia; Le, Linh Khanh; Dam, Anh Vu Trong; Nguyen, Son Hoang; Vu, Thuc Thi Minh; Trinh, Trang Thu Hong; Do, Anh Linh; Do, Ngoc Minh; Le, Trang Huyen; Latkin, Carl; Ho, Roger C. M.; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2022)
Background: This study aims to examine the psychometric properties of the nine-item Patient Health Questionnaire (PHQ-9) and to assess the relationship between the PHQ-9 domain and demographics and health behaviors in Vietnamese people. Method: The PHQ9 was administered to a sample of 899 participants. Exploratory factor and reliability analyses were performed. Tobit regression and Ordered logistic regression were further performed to determine factors associated with the PHQ-9 score and characteristics of depression. Results: The 2-factor model of PHQ-9, including factor 1 “Somatic” and factor 2 “Cognitive/Affective”, showed good psychometric properties. The Cronbach’s alpha value showed high internal consistency in two factors (0.84 and 0.80, respectively). Gender, health behavior exercising, drinking), and health status had associations with both factors of the PHQ-9 model. Conclusion: The PHQ-9 scale is a valid and reliable instrument to assess depression in the Vietnam population. This scale can be a useful screening tool for depression; however, further validation studies in other populations are required. Moreover, the findings revealed that regular health monitoring, physical exercise encouragement, and substance use reduction have a significant impact on the mental health of Vietnamese in suburban areas.